Microwave-assisted extraction optimization of sesquiterpene lactones from Inula helenium roots: A sustainable approach to reduce energy consumption and carbon footprint - Ozcan, Fahriye Seyma; Dikmen, Hilal; Ozcan, Nihat; Cetin, Ozlem; Celik, Mustafa; Trendafilova, Antoaneta (WILEY, 2024)
Inula helenium roots are consumed as natural flavor components and raw or cooked as food, and their extracts are rich in sesquiterpene lactones such as alantolactone (AL) and isoalantolactone (IAL), which have recently attracted great attention due to their pharmacological properties. The industrial utilization of these compounds requires the development of green, efficient, cost-effective, and sustainable extraction protocols. Therefore, this study focused on the optimization of microwave-assisted extraction (MAE) process variables using Face-Centered Central Composite Design (FC-CCD). Then, maceration was applied as a conventional technique, and these techniques were compared in terms of extraction efficiency, morphological changes, antimicrobial activities, carbon emissions, and energy consumption. As a result, optimal MAE conditions, i.e., EtOH: water ratio (X-1) = 100:0, liquid/sample ratio (X-2) = 30:1 mL/g, microwave power (X-3) = 300 W, and irradiation time (X-4) = 5 min, were obtained with AL and IAL yields of 54.99 +/- 0.11 (mg/g) and 48.40 +/- 0.19 (mg/g), respectively. The extract obtained by MAE had similar or better activity than positive controls in most cases and formed the largest inhibition zones against E. coli (29.5 +/- 0.71 mm) and A. niger (34.75 +/- 1.06 mm). Morphological changes of I. helenium roots after extraction were observed by scanning electron microscopy. Additionally, MAE was 43.4 times faster than maceration, resulting in 228.6 times less energy consumption and carbon emissions. Based on these findings, it is recommended to use MAE as an industrial green technique for the extraction of sesquiterpene lactones with potential applications in nutraceuticals and food products in terms of sustainable economy and environmental protection.
Keywords: antimicrobial; carbon emissions; microwave-assisted extraction; optimization; SEM; sesquiterpene lactones; PHENOLIC-COMPOUNDS; ULTRASOUND; ISOALANTOLACTONE; ALANTOLACTONE; Food Science & Technology